Simultaneous measurement of excitation-contraction coupling parameters identifies mechanisms underlying contractile responses of hiPSC-derived cardiomyocytes - Berend J. van Meer (Nature Portfolio, 2019)
Cardiomyocytes obtained from human induced pluripotent stem cells are increasingly used for drug testing, but they are not always predictive of the heart contractile responses. Here the authors develop a method to measure cytosolic calcium, action potentials and contraction simultaneously, to achieve higher sensitivity for drug screenings.